Strategi Manajemen Kepala Sekolah Dalam Meningkatkan Kepercayaan Masyarakat Dan Mutu Pendidikan (Studi Kasus di SMAN 1 Balen Bojonegoro) - Dwi Kasi Kusumawati; Taufiq Haris; Suyitno Suyitno (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to identify and analyze the principal's management strategy, describe the steps of its implementation, and determine the strategic role of the principal in improving public trust and the quality of education at SMA Negeri 1 Balen Bojonegoro. The background of this research is based on the phenomenon of fluctuating public trust in the quality of public schools amidst increasingly competitive inter-institutional competition, which demands management innovation at the education unit level. This research uses a qualitative approach with a descriptive case study type. Data collection was carried out through participatory observation techniques, in-depth interviews with the principal, vice principals, teachers, school committee, and representatives of students' parents, as well as documentation studies on the Strategic Plan and School Profile. Data analysis was operated using the interactive model of Miles, Huberman, and Saldana which includes data condensation, data presentation, and drawing conclusions. The results of the study present three main findings. First, the management strategy relies on the implementation of School-Based Management (SBM) through participatory communication, differentiation of flagship programs (tahfidz program and vocational double track), and optimization of excellent service. Second, strategic steps are implemented comprehensively and systematically through the POAC (Planning, Organizing, Actuating, and Controlling) cycle driven by Education Report Card evaluation data. Third, the principal plays an essential role as a manager, innovator, and motivator by promoting a transformational leadership style. Empirically, the transparency of management governance and the improvement of the quality of graduate services have proven to significantly restore, build, and increase participation and public trust holistically in the existence of SMAN 1 Balen Bojonegoro.